Pengaruh DBR (Debit Banjir Rencana) Terhadap Perancangan Model Saluran untuk Kebutuhan Sistem Penyaliran Tambang PT. Smart Rizqullah Berkah - Muhamad Karnoha Amir; La Ode Dzakir; Hariono Hariono; Aksal Ramadhan Shaddad (Universitas Muslim Indonesia, 2023)
Drainage is a mine drainage channel that every mining company must carry out in fulfilling the implementation of good mining engineering principles. In ensuring that the channel design is following the mine drainage needs, it is necessary to consider several things, one of which is the planned flood discharge. This study focuses on looking at the effect of the planned flood discharge on the design of the drainage channel. The methodology used is the descriptive method, which is data collection based on regional characteristics. The study results were obtained based on several data analyses, namely hydrological risk, planned rainfall, catchment area, runoff discharge, and planned flood discharge. Based on the results of the analysis, the dimensions of the channel based on the runoff are obtained, namely, the depth of the channel is 2.73 meters, the surface width is 6.24 meters, the bottom width is 3.02 meters, the side cross-section width of the channel is 3.23 meters and the water level is 2.63 meters. After being correlated with the planned flood discharge, there is an increase in the average dimensions of 6.4% to a channel depth of 2.95 meters, a surface width of 6.64 meters, a base width of 3.22 meters, and a channel cross-sectional width of 3.43 meters and a face height. water 2.80 meters. Thus, in selecting the channel dimensions, it is recommended to use the channel dimensions correlated with the planned flood discharge to the runoff discharge.